The Role of Foreign Direct Investment and Financial Development on Economic growth of Nepal - Acharya, Santosh (Baneshwor Campus Journal of Academia, 2025)
Foreign direct investment plays an crucial role in economic growth and development especially in developing nations. However, Nepal gets much less foreign direct investment than other developing nations. The primary objective of this research is to investigate how foreign direct investment and financial development affect Nepal’s economic growth. The research used quantitative research method using time series data from 1995/96 to 2021/22. This study used various economic tools such that co-integration analysis, error correction model (ECM), autoregressive distributed lag model (ARDL) and Granger causality econometric methods to anlayze the data. The negative and statistically significant error correction term (ECMt-1) in function confirmed that there is a long run relationship between the variables studied. The estimation of the model shows that approximately 86.1 percent of the variations in economic growth can be explained by independent variables. In the long run FDI as a percentage of GDP has significant positive effect of 8.04 and while in short run, it has insignificant coefficient of 4.07. Domestic credit as a percentage of GDP has significant negative effect of  -0.08 in the long-run and -0.19 in the short-run. The study concludes that foreign direct investment, financial development and gross capital formation all have an impact on Nepal’s economic growth.